Outcomes of isokinetic tests and functional assessment of anterior cruciate ligament reconstruction: Transtibial versus single anatomic femoral tunnel technique - Koray Başdelioğlu; Gökhan Meriç; Zekine Pündük; Devrim Akseki; Aziz Atik; Serdar Sargın (Acta Orthopaedica et Traumatologica Turcica, 2019)
Objective: The aim of the study was to compare the outcomes of the transtibial and anatomical femoral single tunnel surgical techniques in ACL reconstruction. Methods: A total of 30 patients, with 16 patients (15 males and 1 female; mean age: 27.2 ± 7.04) with anatomical femoral single-tunnel technique (AFT) and 14 (12 males and 2 females; mean age: 29.4 ± 8.82) with transtibial technique (TT) were included into the study. All patients were evaluated with isokinetic tests at an angular velocity of 60°/s and 180°/s and the IKDC and Lysholm tests were performed preoperatively and in third, sixth, and 12th months postoperatively. The results were compared between the groups. The mean follow-up time was 17.1 ± 6.48 months. Results: Postoperative third month changes in extension parameters of peak torque (AFT: −93.286, TT: −61.500), peak work (AFT: −77.071, TT: −47.500), peak torque ext/kg (AFT: −1.182, TT: −0.773), peak work ext/kg (AFT: −0.982, TT: −0.604), peak work (AFT: −55.143 TT: −33.063) at an angular velocity of 60°/s and postoperative third month change in extension parameter of peak power (AFT: −86.786 TT: −54.875) at an angular velocity of 180°/s were found to be better in the transtibial group (p < 0.05) and postoperative sixth month peak torque (AFT: 1.429, TT: −5.688) value at an angular velocity of 60°/s was found to be less in the anatomical femoral single-tunnel group (p < 0.05). The IKDC (AFT: 94.671, TT: 90.025) (p < 0.05) and Lysholm (AFT: 96.714, TT: 92.375) (p < 0.05) scores of the anatomical femoral single-tunnel group were better than the transtibial group regarding to the postoperative final follow-up. There are positive intermediate correlations between preoperative IKDC and Lysholm scores with preoperative and postoperative some isokinetic test ratio (r = 0.539; p = 0.031), and preoperative peak power extension (r = 0.541; p = 0.030) at the both angular velocity of 60°/s and 180°/s in the transtibial group. There was no significant difference between the two groups with regards to the Lachman, anterior drawer and pivot shift tests (p < 0.05). Conclusion: There were differences in terms of isokinetic parameters in early outcomes but there was no statistical difference between isokinetic parameters at the end of 1st year between two groups. There were some correlations between IKDC and Lysholm scores with some isokinetic parameters. Level of Evidence: Level III, Therapeutic Study. Keywords: Knee joint, Anterior cruciate ligament, Reconstruction, Isokinetic test, Functional test, Transtibial, Anatomic tunnel